Acoustic microscopy - Briggs, Andrew; Kolosov, O. V. (Oleg V.) (Oxford : Oxford University Press, 2010)
For many years 'Acoustic Microscopy' has been the definitive book on the subject. A key development since it was first published has been the development of ultrasonic force microscopy. This edition has a major new chapter on this technique and its applications.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Materials -- Microscopy; Acoustic microscopy